2014
DOI: 10.1186/1476-4598-13-236
|View full text |Cite
|
Sign up to set email alerts
|

Cyr61 promotes epithelial-mesenchymal transition and tumor metastasis of osteosarcoma by Raf-1/MEK/ERK/Elk-1/TWIST-1 signaling pathway

Abstract: BackgroundOsteosarcoma is the most common primary malignant tumor in children and young adults, and its treatment requires effective therapeutic approaches because of a high mortality rate for lung metastasis. Epithelial to mesenchymal transition (EMT) has received considerable attention as a conceptual paradigm for explaining the invasive and metastatic behavior during cancer progression. The cysteine-rich angiogenic inducer 61 (Cyr61) gene, a member of the CCN gene family, is responsible for the secretion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 55 publications
2
91
0
2
Order By: Relevance
“…It is possible that IGFBP10/CYR61/CCN1 can suppress hepatocarcinogenesis by inhibiting compensatory proliferation [34], although its role in tumor growth is not well established yet. At the same time, an increased level of CYR61/CCN1 as well as a decreased level of NOV/CCN3 possibly has relation to increased metastasis of glioma cells without IRE1 function [40], because CYR61/CCN1 is responsible for induction of the tumor epithelial-mesenchymal transition, invasion, and metastasis as well as inhibition of NOV levels promotes the invasive phenotype of metastatic cancer cells [35]. Furthermore, elevated levels of WISP1 and CYR61 in primary breast cancers associated with more advanced features [14].…”
Section: Fig 4 Effect Of Hypoxia On the Expression Of Insulinlike Gmentioning
confidence: 99%
“…It is possible that IGFBP10/CYR61/CCN1 can suppress hepatocarcinogenesis by inhibiting compensatory proliferation [34], although its role in tumor growth is not well established yet. At the same time, an increased level of CYR61/CCN1 as well as a decreased level of NOV/CCN3 possibly has relation to increased metastasis of glioma cells without IRE1 function [40], because CYR61/CCN1 is responsible for induction of the tumor epithelial-mesenchymal transition, invasion, and metastasis as well as inhibition of NOV levels promotes the invasive phenotype of metastatic cancer cells [35]. Furthermore, elevated levels of WISP1 and CYR61 in primary breast cancers associated with more advanced features [14].…”
Section: Fig 4 Effect Of Hypoxia On the Expression Of Insulinlike Gmentioning
confidence: 99%
“…Cyr61 is up regulated in many cancers, such as breast [19], esophagus [22], and colorectal cancers [23]. Several studies have reported that Cyr61 promotes the EMT and tumor metastasis [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have aimed to develop specific therapeutic approaches targeting metastatic progression, and to understand the mechanisms underlying metastasis (4,5). Cysteine-rich angiogenic inducer 61 has been reported to promote the epithelial to mesenchymal transition of osteosarcoma (6). In addition, Ezrin expression has been reported to be necessary for metastasis of osteosarcoma (7), and high expression levels of transforming growth factor-β (TGF-β) have been observed in osteosarcoma cell lines (8).…”
Section: Introductionmentioning
confidence: 99%